Cross-cultural impacts of COVID-19 on higher education learning and teaching practices in Spain, Oman, Nigeria and Cambodia: A cross-cultural study - Cifuentes-Faura, Javier; Obor, Deborah Odu; To, Loeurt; Al-Naabi, Ishaq (Journal of University Teaching and Learning Practice, 2021)
Adapting new learning and teaching practices during COVID-19 pandemic has impacted students’ learning in higher education. Using a cross-sectional research methodology, the study attempted to understand the cross-cultural impacts of COVID-19 on higher education students in Cambodia, Nigeria, Oman and Spain to determine the changes that COVID-19 has brought about in higher education students; examine how students' learning behaviour and attitudes have changed during COVID-19; identify the challenges they have experienced; and identify the changes that have taken place in learning and teaching in the selected countries. A total sample of 242 students was randomly selected from four higher education institutions in each of the selected countries. The study provided a cross-cultural understanding of how COVID-19 has affected students’ well-being, behaviors and learning. The results show that COVID-19 had adverse effects on the well-being of students in the four countries. Students received inadequate social support and security protection from others and instructors when they needed it. Omani students received less social support compared with the other three countries. COVID-19 had the worse effect on students’ employment in the four countries. The effect pressed much concern on Nigerian students who experience a great job loss. Students from the four countries were required to put a lot of effort and energy to fulfil the requirements in the program.